Effects of motivational self-talk on endurance and cognitive performance in the heat - Wallace, P. J.; McKinlay, B. J.; Coletta, N. A.; Vlaar, J. I.; Taber, M. J.; Wilson, P. M.; Cheung, S. (Medicine & Science in Sports & Exercise, 2017)
Purpose: We tested the effectiveness of a 2-wk motivational self-talk (MST) intervention—specific to heat tolerance—on endurance capacity and cognitive function in the heat.